Avaliação físico-química e sensorial de caldo de cana-de-açúcar - Soares, Eduardo Alessandro (2017)
This study aimed to evaluate the physicochemical and sensory characteristics of sugarcane juice (garapa) of seven varieties RB (Republic of Brazil) and correlate agronomic important aspects for obtaining garapa. The garapas were analyzed for pH, acetic acidity, Brix, Pol purity, color, turbidity and reducing sugars. The sequence of sample testing included the parameters: color, sweet taste, body, flavor and preference. The physicochemical results showed significant differences a higher preference for the RB855453 and RB935744 varieties, with no differences between them (5% statistical probability). In relation to body attributes, sweet taste and preference there was among varieties in pH attributes, acetic acidity, Brix, purity, color, turbidity and reducing sugars. The analyzed varieties were not significantly different for the Pol attribute. Sensory analysis showed that in relation to the color attribute varieties RB855156, RB867515 and RB965917 proved to be lighter. Regarding the flavor attribute there was no significant difference among the varieties. Regarding the agronomic aspects available in the national catalogue of RB varieties, the studied varieties presented satisfactory characteristics in relation to the fiber content, agricultural productivity and harvest season. In addition, most are resistant to the main diseases of the culture.